Polymorphism in flower colour and petal type in Aparajita (Clitoria ternatea) (Open Access Journal of Medicinal and Aromatic Plants, 2013)
Clitoria ternatea L., belonging to Fabaceae family is a very well known Ayurvedic medicinal plant used for different ailments. It is commonly called Butterfly pea or Conch flower or ‘Aparajita’. The species is believed to be a native of the Caribbean, Central America and Mexico, but is now naturalised all over the tropical parts of India. The plant bears solitary, axillary, papilionaceous flowers. The fresh root is slightly bitter and acrid in taste. In the Indian systems of medicines particularly in Ayurveda, roots, seeds and leaves of the species have long been used as brain tonic and is believed to promote memory and intelligence (Mukherjee et al., 2008). The leaves and roots are used in the treatment of a number of ailments including body aches, especially infections, urinogenital disorders, and as an anthelmintic and antidote to animal stings (Nirmal et al., 2008). The major phyto-constituents found in Clitoria ternatea are the pentacyclic triterpenoids such as taraxerol and taraxerone (Banerjee & Chakravarti 1963, 1964; Uma et al., 2009).